Ad-Din Fi Qulub: o Islam em São Paulo (1950-1980) - Nakashima, Henry Albert Yukio (2012)
From the second half of the 19th Century, migratory movements brought to Brazil people called "Arabs". Syrians, Lebanese, Palestinians and other nationalities who, due to social political economic conjunctures in their region, decided to come into other lands adventures. They left behind their families, they brought in the luggage longings, hopes, culture and religion. In Brazilian land - specifically in Sao Paulo, the case of this work they were established, they remained longer, they were adapted. This study investigated the adapting process, by which one of the immigrants religious practices, Islam, from the second half of the 20th Century, to São Paulo City. In the same way, as this practice, so different from local cultures, served as identity contribution for these people, besides being their Allah connection. The used instrument was the Muslims memory who lived in such period. From their interviews, the goal was to disclose this process. I take a place for history and fundamentals of this religion, and their presence in the Iberian peninsula, and also among African slaves in Brazil, stating that relationship between Islam and ourselves goes beyond any assumption. Among the whole existing Paulicéia cultural richness, Islam can not be ignored. The title in Arabic means: the religion is in the heart . This sentence is a quote from an immigrant who thinks that religion is beyond the adjustments which it has to pass through during the history. The idea summarizes the work